From Focused Thought to Reveries: A Memory System for a Conscious Robot - Balkenius, Christian; Tjøstheim, Trond A.; Johansson, Birger; Gärdenfors, Peter (Frontiers in Robotics and AI, 2018)
We introduce a memory model for robots that can account for many aspects of an inner world, ranging from object permanence, episodic memory and planning to imagination and reveries. It is modeled after neurophysiological data and includes parts of the cerebral cortex together with models of arousal systems that are relevant for consciousness. The three central components are an identification network, a localization network and a working memory network. Attention serves as the interface between the inner and the external world. It directs the flow of information from sensory organs to memory, as well as controlling top-down influences on perception. It also compares external sensations to internal top-down expectations. The model is tested in a number of computer simulations that illustrate how it can operate as a component in various cognitive tasks including perception, the A-not-B test, delayed matching to sample, episodic recall and vicarious trial-and-error.